Evaluation and monitoring platform and its effect on the quantitative indicators of the thesis review process - Valles Coral, Miguel A. (2019)
To elaborate, review and correct a thesis project to choose the professional title is an important task. However, the fulfilment with the deadlines by those involved in the different stages of the process is not guaranteed by their busy work. The research objective was to implement an IC platform for the control of quantitative indicators of research management since 2018, allowing that interested parties know their performance indicators in fulfilment with deadlines, which impacted on the quantitative aspects of the review process. To that end, a study was made of the processes of the general regulation of research, identification of indicators and implementation of a platform for evaluation and monitoring of research projects from the registration process, review, notifications of changes of status to the presentation of tactical and strategic quantitative reports. The most important result of the research study is that it has managed to improve the performance of 10 indicators identified on average by up to 55%, concluding that the results of the management of the research quantitative indicators have been optimized at the San Martín National University - Tarapoto.